Final report - EngageBook: touch, read and play - Zagalo, Nelson (2015)
This  report  intends  to  give  a  detailed  notion  about  the  entire  project  development  from  its  publications to communications; from the workshops to the software and BridgingBook patent. To make it clear we followed the Tasks timeline as presented in our proposal, adjusting dates, when they were changed. Because we followed a double take in prototyping/software development, we will also repeat some of the tasks in order to give information about each different phase and its dimensions, in an autonomous way.